Single Cell RNA-seq Data Analysis Reveals the Potential Risk of SARS-CoV-2 Infection Among Different Respiratory System Conditions - Zhang, Qiang; Yue, Yuanyi; Tan, Huiwen; Liu, Yishu; Zeng, Yin; Xiao, Li (Frontiers in Genetics, 2020)
COVID-19 (Coronavirus Disease 2019) has been an ongoing pandemic, resulting in increasing people infected globally. Understanding the potential risk of infection for people under different respiratory system conditions is important and will help prevent disease spreading. We explored and collected five published and one unpublished single cell respiratory system tissue transcriptome datasets, including Idiopathic Pulmonary Fibrosis (IPF), aging lungs (mouse origin data), lung cancers, smoked branchial epithelium, and Chronic obstructive pulmonary disease (COPD), for specifically re-analyzing the ACE2 and TMPRSS2 expression profiles.Compared to the normal people, we found that smoking and lung cancer increases the risk for COVID-19 infection due to a higher expression of ACE2 and TMPRSS2 in lung cells. Aged lung does not show increased risk for infection. IPF patients may have lower risk for original COVID-19 infection due to lower expression in AT2 cells, but may have a higher risk for severity due to more comprehensive expression of TMPRSS2.Further investigation and validation on these cell types are required. Nonetheless, this is the first report to predict the risk and potential severity for COVID-19 infection for people with different respiratory system conditions. Our analysis is the first mechanistical report to illustrate how the underlying respiratory system conditions contribute to a higher infection risk.